Artistic Expression of Harvest Ceremony Ritual of Wehea Dayak Tribe - Sutarya, Abdul Majid; Winata, Gita (Gorga : Jurnal Seni Rupa, 2025)
The Lom Plai harvest ceremony ritual is an essential tradition of the Wehea Dayak tribe in East Kalimantan that combines artistic expression with spiritual and social values. However, in-depth studies on the form and meaning of artistic expression in this ritual are still limited. This study aims to describe how visual elements such as costumes, masks, colours, motifs, musical instruments, and spatial and dance movement patterns play a role in strengthening the cultural and spiritual identity of the Dayak Wehea community. The method used is a descriptive qualitative approach with a visual ethnography model through participatory observation, in-depth interviews, and visual documentation in Nehas Liah Bing Village, East Kutai. Thematic analysis based on symbolic theory and cultural structure was used to interpret the symbolic meaning of artistic expression elements. The results show that artistic expression in the Lom Plai ritual functions as a medium of spiritual communication that strengthens human relationships with nature and ancestors and strengthens social solidarity and preservation of cultural values amid modernization.